Plasmonic super-oscillations and sub-diffraction focusing - Yuan, Guanghui (2018)
We demonstrate experimental focusing of surface plasmon polaritons beyond the plasmon diffraction limit using a super-oscillatory plasmonic antenna at the wavelength of 785nm, achieving a hot-spot as small as 300nm.